Prospects for Investigative Reporting in Private Media Organization in Nigeria: A Case Study of Unity FM and Al’barka Radio - Abdullahi, Shehu Abdulkadir; Olanase, Sarah Oluwadamilola (ALSYSTECH Journal of Education Technology, 2024)
This research work was conducted in order to determine the Prospects for Investigative Reporting in Private Media outlets in Bauchi and Jos. The objective of the study was to find out whether the two private radio stations (Unity FM, Albarka Radio) in Jos and Bauchi do practice Investigative Journalism. A qualitative, cross-sectional survey was employed for the study. In-depth interview was used as means of data collection from a purposively sample of six radio journalists, consisting of two editor and four reporters. Following from the social responsibility and surveillance theoretical discourse, findings revealed that both the radio stations in Jos and Bauchi do practice Investigative Journalism and are also training young minds on the beat. This research work recommends that the practical aspect of the course should receive more attention than the theoretical part in tertiary institutions, there should be constant training, retraining and retraining staff in each media organization and also adequate budgets of funds should be put into considerations by the management of any media organization.